Quiet Quitter, Myth or Fact? Measuring Employee Engagement on Aviation Education - Andi Frianto Peranginangin; Agung Wahyu Wicaksono (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2023)
Organizational achievement of its vision and mission is supported by the level of employee engagement in the process. Employee engagement is directly proportional to employee performance, where em-ployees who perform well will always involve themselves with their work and duties. This study aims to measure employee engagement which is influenced by employee well-being, work environment, and, job design at the Air Transportation Human Resources Development Center which consists of 9 schools in Indonesia. Mixed methods were chosen in this study to provide a complete picture of employee engage-ment. The quantitative method uses SEM-PLS analysis with the SmartPLS3 tool which is strengthened by the results of collecting perceptions with open questions using qualitative methods. The results of the study show that employee well-being and job design influence employee engagement while the work environment fails to influence employee engagement. This study also proves that employee well-being can mediate the relationship between job design and work environment with employee engagement. The most dominant indicators of employee engagement are professionalism, comfort for employee well-being, and co-workers for the work environment while work design is dominated by work identity and ability variations.